PUBLIC-PRIVATE PARTNERSHIP IN THE DEVELOPMENT OF SHALE GAS RESOURCES IN UKRAINE - Vytvitskyi, Y. S. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2019)
The article considers the possibilities of using the institution of public-private partnership in the development of natural gas resources from shale formations. The economic expediency of using public-private partnership in the development of these resources is due to the need to overcome deficiencies in the existing system of nature management and the use of an effective institute of civil ownership of natural resources. Features of public-private partnership in the development of natural resources, the possibility of applying various types of transactions, methodical approaches to the formation of information necessary for their conclusion, relating to the content of gas in slate formations, forecasting the productivity of wells, the marginal cost limits, at which a profitable extraction of shale gas is possible , capitalization of shale gas resources. The criteria for the selection of the most promising zones of "sweeps spots" (sweet places) are established on significant areas of their distribution, which is the main task of exploration for the purpose of exploration, exploration and extraction of shale gas. It was investigated that the institutions of financing shale gas extraction are important in concluding public-private partnership agreements, the key role of which is the capitalization of natural resources - the process of conversion of factors of production into capital. The method of capitalization of shale gas resources in the subsoil is described, which will enable application of the concept of project investment. The directions of perfection of the institute of public-private partnership during development of shale gas resources are determined. Key words: public-private partnership, shale gas, characteristics of shale formations, gas content, wells productivity, the cost of unprofitable shale gas extraction, investment efficiency, capitalization of shale gas resources.